Integrative systematics of the scleractinian coral genera Caulastraea, Erythrastrea and Oulophyllia. (2nd March 2021) - Arrigoni, Roberto; Huang, Danwei; Berumen, Michael L.; Budd, Ann F.; Montano, Simone; Richards, Zoe T.; Terraneo, Tullia I.; Benzoni, Francesca
Abstract: Modern systematics integrating molecular and morphological data has greatly improved our understanding of coral evolutionary relationships during the last two decades and led to a deeply revised taxonomy of the order Scleractinia. The family Merulinidae (Cnidaria: Scleractinia) was recently subjected to a series of revisions following this integrated approach but the phylogenetic affinities of several genera ascribed to it remain unknown. Here, we partially fill this gap through the study of 89 specimens belonging to all 10 valid species from four genera ( Caulastraea, Erythrastrea, Oulophyllia and Dipsastraea ) collected from 14 localities across the Indo‐Pacific realm. Four molecular loci (histone H3, COI, ITS and IGR) were sequenced, and a total of 44 skeletal morphological characters (macromorphology, micromorphology and microstructure) were analysed. Molecular phylogenetic analyses revealed that the phaceloid Caulastraea species are split into two distinct lineages. A species previously ascribed to the genus Dipsastraea, Dipsastraea maxima, is also recovered in one on these lineages. Furthermore, Erythrastrea is nested within Oulophyllia . The molecular reconstructions of evolutionary relationships are further corroborated by multiscale morphological evidence. To resolve the taxonomy of these genera, Astraeosmilia is resurrected to accommodate Astraeosmilia connata, Astraeosmilia curvata, Astraeosmilia tumida and Astraeosmilia maxima, with Caulastraea retaining Caulastraea furcata and Caulastraea echinulata . Based on the examination of type material, Erythrastrea flabellata is considered an objective synonym of Lobophyllia wellsi, which is transferred to Oulophyllia following the obtained morpho‐molecular results. This work further confirms that an integrated morpho‐molecular approach based on a rigorous phylogenetic framework is fundamental for an objective classification that reflects the evolutionary history of scleractinian corals.